Mothers’ experience of maternity and neonatal care when babies die: A quantitative study - Redshaw, M; Henderson, J (Public Library of Science, 2018)
Background The death of a newborn baby is devastating. While clinical issues may be a primary concern, interpersonal aspects can impact significantly. Mothers in this situation are not easy to access for research and little quantitative evidence is available. In this study we aimed to describe their experience of care, emphasising associations with infant gestational age. Methods Secondary analysis of population-based survey data collected through the Office for National Statistics following neonatal death in England in 2012–13. Women were asked about clinical events and care during pregnancy, labour and birth, when the baby died, postnatally and in the neonatal unit. Results 249 mothers returned completed questionnaires (30% response rate), 50% of births were at 28 weeks’ gestation or less and 66% had babies admitted for neonatal care. 24% of women were left alone and worried during labour and 18% after birth. Only 49% felt sufficiently involved in decision-making at this time. Postnatally only 53% were cared for away from other mothers and babies, 47% could not have their partner stay with them, and 55% were not located close to their baby. Mothers of term babies were significantly less likely to report confidence in staff, feeling listened to and having concerns taken seriously during labour, and postnatally many felt insufficiently informed about their baby’s condition, and that neonatal staff were not always aware of parental needs. However, most mothers (84%) were satisfied with neonatal care. Conclusions There is room for improvement if women whose babies die in the neonatal period are to receive the care and support they need. Women who have a baby admitted to a neonatal unit should be cared for nearby, with room for their partner and with greater involvement in decision-making, particularly where withdrawal of life support is considered.